2019
DOI: 10.2196/12530
|View full text |Cite
|
Sign up to set email alerts
|

Internet-Delivered Acceptance and Commitment Therapy for Anxiety Treatment: Systematic Review

Abstract: Background Anxiety conditions are debilitating and prevalent throughout the world. Acceptance and Commitment Therapy (ACT) is an effective, acceptance-based behavioral therapy for anxiety. However, there are treatment barriers (eg, financial, geographical, and attitudinal), which prevent people from accessing it. To overcome these barriers, internet-delivered ACT (iACT) interventions have been developed in recent years. These interventions use websites to deliver ACT information and skill training… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 54 publications
(133 reference statements)
5
63
1
2
Order By: Relevance
“…The present study indicated that the efforts made to increase women's communication skills would be associated with their improved psychological health and increased marital satisfaction. Many studies have shown that communication skill training is effective in reducing marital conflicts [19,20] and improving the communication between couples [16], and improves the couples' psychological health [13,21]. During pregnancy, due to physical and emotional changes in women, abnormal relationships may be experienced by the couples [2]; however, this study confirmed that during pregnancy, like other periods of life, communication skills training for women can improve such communications and relationships.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…The present study indicated that the efforts made to increase women's communication skills would be associated with their improved psychological health and increased marital satisfaction. Many studies have shown that communication skill training is effective in reducing marital conflicts [19,20] and improving the communication between couples [16], and improves the couples' psychological health [13,21]. During pregnancy, due to physical and emotional changes in women, abnormal relationships may be experienced by the couples [2]; however, this study confirmed that during pregnancy, like other periods of life, communication skills training for women can improve such communications and relationships.…”
Section: Discussionsupporting
confidence: 63%
“…The communication skills training package with the couple-based intervention was developed based on the documents [14][15][16] as well as the opinions of experts on psychology, psychiatry and reproductive health. For example, a psychologist believed that to improve the couple's relationship, the couples' mutual understanding of each other's feelings and conditions are necessary factor.…”
Section: Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…in this population is felt. 26,27 As several studies have supported the effectiveness of ACT in reducing the symptoms of depression, anxiety and stress, [28][29][30] the present study aimed to determine the efficacy of ACT compared to routine educations and care provided in community therapeutic center on emotional distress in the elderly with type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Das primäre Ziel von ACT ist nicht, die Angstsymptome zu reduzieren, sondern die psychische Flexibilität zu erhöhen, also sich bewusst dem gegenwärtigen Moment zu stellen und werteorientiert zu handeln [20]. Ein wichtiger Prozess ist dabei die kognitive Defusion, die Fähigkeit, sich von den eigenen Gedanken zu lösen und diese distanziert zu betrachten.…”
Section: Acceptance and Commitment Therapy (Act)unclassified